2017
DOI: 10.1515/jpem-2016-0147
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health-related quality of life in Egyptian adolescents with type 1 diabetes: DEMPU survey

Abstract: QoL had a variable significant association with certain socio-demographic and clinical characteristics of diabetics (sex, residence, educational level as well as metabolic control).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
3
9
0
8
Order By: Relevance
“…Regarding the effect of body mass index on HRQOL, current results were in agreement with the studies of Schwimmer et al 2003 andWilliams et al 2005, but in contrast to the current findings, no significant differences in HRQOL by BMI category demonstrated by the studies of Naughton et al 2008, Lawrence et al 2012, and Hassan et al 2017 In the current study, negative statistically significant correlations were found between HRQOL domains (Pediatric Quality of Life Inventory scores) with all metabolic control parameters (MRBG, HbA1c, number of DKA, number of hypoglycemic attacks, and number of hospitalization due to acute diabetic complications); the strongest relation was between treatment adherence scale with HbA1c% (r = − 0.941, p ˂ 0.001), but no significant correlation found with mean insulin dose in the studied diabetic patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding the effect of body mass index on HRQOL, current results were in agreement with the studies of Schwimmer et al 2003 andWilliams et al 2005, but in contrast to the current findings, no significant differences in HRQOL by BMI category demonstrated by the studies of Naughton et al 2008, Lawrence et al 2012, and Hassan et al 2017 In the current study, negative statistically significant correlations were found between HRQOL domains (Pediatric Quality of Life Inventory scores) with all metabolic control parameters (MRBG, HbA1c, number of DKA, number of hypoglycemic attacks, and number of hospitalization due to acute diabetic complications); the strongest relation was between treatment adherence scale with HbA1c% (r = − 0.941, p ˂ 0.001), but no significant correlation found with mean insulin dose in the studied diabetic patients.…”
Section: Discussionsupporting
confidence: 89%
“…The negative impact of long diabetes duration on quality of life might result from significant deterioration in glycemic control, deterioration in treatment adherence over this time, and occurrence of long-term diabetes complications that reduce person's perception of well-being and productivity. On the other hand, the studies of Stahl et al 2012, Lawrence et al 2012, Abd-Elall et al 2016, and M. Hassan et al 2017 stated that duration of diabetes had no statistically significant effect on QOL.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in Kuwait, Abdul-Rasoul, AlOtaibi, Abdulla, Rahme, and AlShawaf (2013) reported lower total generic QoL in children with T1D than healthy controls. Furthermore, various factors have been proposed to be important predictors for lower QoL such as female gender, longer diabetes duration, age, poor glycemic control, and economic class (Hassan, Musa, Hai, Fathy, & Ibrahim, 2017;Kalyva, Malakonaki, Eiser, & Mamoulakis, 2011;Lukács & Barkai, 2013).…”
Section: Healthmentioning
confidence: 99%
“…Los artículos incluidos en el estudio para su análisis son 25 (tablas 1 y 2) y la mayoría fueron obtenidos desde la base de datos bibliográfica MEDLINE. El inglés fue el idioma predominante [13][14][15][16][17][18][19][20][21][22][24][25][26][27][28][29][30][31][32][33][34][35] y en el año 2018 fueron publicados la mayor parte de ellos, 7 (28%) [30][31][32][33][34][35][36] . La revista académica más utilizada para la publicación de los artículos fue la Pediatric Diabetes 15,26,31,33 .…”
Section: Resultsunclassified